Rapid 18F-FDG Uptake in Brain of Awake, Behaving Rat and Anesthetized Chicken has Implications for Behavioral PET Studies in Species With High Metabolisms - Gold, Maria E. L.; Norell, Mark A.; Budassi, Michael; Vaska, Paul; Schulz, Daniela (Frontiers in Behavioral Neuroscience, 2018)
Brain-behavior studies using 18F-FDG PET aim to reveal brain regions that become active during behavior. In standard protocols, 18F-FDG is injected, the behavior is executed during 30–60 min of tracer uptake, and then the animal is anesthetized and scanned. Hence, the uptake of 18F-FDG is not itself observed and could, in fact, be complete in very little time. This has implications for behavioral studies because uptake is assumed to reflect concurrent behavior. Here, we utilized a new, miniature PET scanner termed RatCAP to measure uptake simultaneously with behavior. We employed a novel injection protocol in which we administered 18F-FDG (i.v.) four times over two 2 h to allow for repeated measurements and the correlation of changes in uptake and behavioral activity. Furthermore, using standard PET methods, we explored the effects of injection route on uptake time in chickens, a model for avians, for which PET studies are just beginning. We found that in the awake, behaving rat most of the 18F-FDG uptake occurred within minutes and overlapped to a large extent with 18F-FDG data taken from longer uptake periods. By contrast, behavior which occurred within minutes of the 18F-FDG infusion differed markedly from the behavior that occurred during later uptake periods. Accordingly, we found that changes in 18F-FDG uptake in the striatum, motor cortex and cerebellum relative to different reference regions significantly predicted changes in behavioral activity during the scan, if the time bins used for correlation were near the injection times of 18F-FDG. However, when morphine was also injected during the scan, which completely abolished behavioral activity for over 50 min, a large proportion of the variance in behavioral activity was also explained by the uptake data from the entire scan. In anesthetized chickens, tracer uptake was complete in about 80 min with s.c. injection, but 8 min with i.v. injection. In conclusion, uptake time needs to be taken into account to more accurately correlate PET and behavioral data in mammals and avians. Additionally, RatCAP together with multiple, successive injections of 18F-FDG may be useful to explore changes in uptake over time in relation to changes in behavior.